Berries extracts as natural antioxidants in meat products: A review. (April 2018) - Lorenzo, José Manuel; Pateiro, Mirian; Domínguez, Rubén; Barba, Francisco J.; Putnik, Predrag; Kovačević, Danijela Bursać; Shpigelman, Avi; Granato, Daniel; Franco, Daniel
Abstract: The aim was to evaluate antioxidants from berries as replacement food additives for inhibition of lipid and protein oxidation in meat and meat products, since meats are highly susceptible to oxidation. Oxidation can be delayed/retarded by synthetic antioxidants with phenolic structures (e.g. butylated hydroxytoluene). However, new natural alternatives are needed for synthetic antioxidants due to the controversy regarding their possible negative health effects and consumers' demand for more 'natural' food additives. Berries are a good source of phenolic compounds, especially anthocyanins, which can be used as the potential alternative. Reviewed berries included bearberry ( Arctostaphylos sp.), blueberry ( Vaccinium sp.), blackberry ( Rubus sp.), blackcurrant ( Ribes nigrum ), cranberry ( Vaccinium sp.), cloudberry ( Rubus chamaemorus ), strawberry ( Fragaria ananassa), and grape berries ( Vitis sp.). Data implied that blueberries, blackberries, cranberries, and grapes can be useful for replacing/decreasing synthetic antioxidants in meat products. Their extracts have antioxidant polyphenols with health benefits that are useful for stabilizing meat products. Graphical abstract: Image 1 Highlights: Review evaluated the effects of natural berry extracts on meat oxidation. Lipids/proteins oxidation causes quality losses and health risks from MDA. Synthetic antioxidants are unpopular and potentially harmful. Berry extracts (e.g. grape, blackcurrant) can replace synthetic antioxidants. Berry extracts are requested by the market and provide added value in products.